Tumor Sprouting in Papillary Thyroid Carcinoma Is Correlated with Lymph Node Metastasis and Recurrence - Lee, Eunjung (The Korean Society of Pathologists and The Korean Society for Cytopathology, 2014)
BACKGROUND: Identification of poor prognostic factors in papillary thyroid carcinoma (PTC) patients is important for the patients' care and follow-up. We can sometimes see small tumor clusters without desmoplasia and no evidence of lymphatic emboli around the main tumor mass of PTC. We termed this form of tumor clustering, 'tumor sprouting,' and determined whether these tumors correlate with lymphovascular invasion, lymph node metastasis, and recurrence. METHODS: We analyzed a total of 204 cases of papillary thyroid macrocarcinoma. Number, size and distance from the main tumor of the tumor sprouting were observed and analyzed with clinicopathologic characteristics. RESULTS: Tumor sprouting was observed in 101 patients. Presence of tumor sprouting was significantly associated with positive resection margin (p=.002), lymphovascular invasion (p=.001), lymph node metastasis (p<.001), and recurrence (p=.004). Univariate analysis of recurrence-free survival revealed that tumor multiplicity (p=.037), positive resection margin (p=.007), lymphovascular invasion (p=.004), lymph node metastasis (p<.001), and tumor sprouting (p=.004) were poor prognostic factors. In multivariate analysis, positive resection margin was an independent poor prognostic factor of recurrence. CONCLUSIONS: In conclusion, tumor sprouting is significantly correlated with lymph node metastasis and recurrence. Evaluation of tumor sprouting in PTC patients could be helpful in predicting tumor recurrence or lymph node metastasis.